Remote ischemic preconditioning inhibits platelet αIIbβ3 activation in coronary artery disease patients receiving dual antiplatelet therapy: A randomized trial. (13th March 2020) - Lau, Jerrett K.; Pennings, Gabrielle J.; Reddel, Caroline J.; Campbell, Heather; Liang, Hai Po H.; Traini, Mathew; Gardiner, Elizabeth E.; Yong, Andy S.; Chen, Vivien M.; Kritharides, Leonard
Abstract: Objectives: We investigated whether remote ischemic preconditioning (RIPC) inhibits agonist‐induced conformational activation of platelet αIIb β3 in patients with coronary artery disease already receiving conventional antiplatelet therapy. Patients/Methods: Consecutive patients with angiographically confirmed coronary artery disease were randomized to RIPC or sham treatment. Venous blood was collected before and immediately after RIPC/sham. Platelet aggregometry (ADP, arachidonic acid) and whole blood platelet flow cytometry was performed for CD62P, CD63, active αIIb β3 (PAC‐1 binding) before and after stimulation with ADP, thrombin ± collagen, or PAR‐1 thrombin receptor agonist. Results: Patients (25 RIPC, 23 sham) were well matched, 83% male, age (mean ± standard deviation) 63.3 ± 13.2 years, 95% aspirin, 81% P2Y12 inhibitor. RIPC did not affect platelet aggregation, nor agonist‐induced expression of CD62P, but selectively and significantly decreased αIIb β3 activation after stimulation with either PAR‐1 agonist peptide or the combination of thrombin + collagen, but not after ADP nor thrombin alone. The effect of RIPC on platelet αIIb β3 activation was evident in patients receiving both aspirin and P2Y12 inhibitor, and was not associated with an increase in vasodilator‐stimulated phosphoprotein phosphorylation. Conclusions: Remote ischemic preconditioning inhibits conformational activation of platelet αIIb β3 in response to exposure to thrombin and collagen in patients with coronary artery disease receiving dual antiplatelet therapy. These findings indicate agonist‐specific inhibition of platelet activation by RIPC in coronary artery disease that is not obviated by the prior use of P2Y12 inhibitors.